UPAYA MENINGKATKAN KINERJA ANGGOTA POLRI BAGIAN SUMBER DAYA MANUSIA DI POLRES MAGELANG KOTA - Siti Makbul; Awal Satrio Nugroho; Zulkifli Zulkifli (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
This study uses a qualitative research method with a descriptive design. The subjects in this study were a total of 4 people consisting of 1 person from the Head of the Sumda Division, and 3 members of the National Police, namely 1 Kasubbagwatpers SDM Division, 1 Kasubbagdalpers SDM Division. HR and 1 member of the National Police at the Magelang City Police Station. The object of this research is an effort to improve the performance of members. The results of this study explain that the performance of members of the National Police for Human Resources at the Magelang City Police less than optimal because due to a lack of personnel and the lack of basic skills and abilities possessed by personnel, then efforts to improve the performance of members of the National Police for Human Resources at the Magelang City Police by attending appropriate training. With individual conditions and the needs of their duties, the Head of the Human Resources Division of the Magelang City Police in the policy-making process. Improving the performance of its members, making policies carefully, transparently, accountable, and professionally.